2015
DOI: 10.1111/trf.13123
|View full text |Cite
|
Sign up to set email alerts
|

In vitro study of platelet function confirms the contribution of the ultraviolet B (UVB) radiation in the lesions observed in riboflavin/UVB‐treated platelet concentrates

Abstract: The amotosalen/UVA-treated PCs confirmed previously published results with a slight increase of PSLs compared to untreated PCs. Riboflavin/UVB-treated PCs present significant in vitro PSLs compared to untreated PCs. These lesions are caused by the UVB radiation alone and probably involve the generation of reactive oxygen species. The impact of these observations on clinical use must be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
49
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(61 citation statements)
references
References 87 publications
11
49
1
Order By: Relevance
“…Our lab has demonstrated the effects of PITs on oxidative processes in platelets by showing an important decrease in extracellular antioxidant power after INTERCEPT ® treatment; the same effects were seen with our laboratory’s in-house riboflavin/UVB system [24]. Antioxidant power was measured electrochemically using EDEL technology (in arbitrary units equivalent to one micromolar ascorbic acid) by deposing a 2 µL drop of liquid sample on a microchip.…”
Section: The Overlap Of Redox Proteomics and Transfusionmentioning
confidence: 98%
See 2 more Smart Citations
“…Our lab has demonstrated the effects of PITs on oxidative processes in platelets by showing an important decrease in extracellular antioxidant power after INTERCEPT ® treatment; the same effects were seen with our laboratory’s in-house riboflavin/UVB system [24]. Antioxidant power was measured electrochemically using EDEL technology (in arbitrary units equivalent to one micromolar ascorbic acid) by deposing a 2 µL drop of liquid sample on a microchip.…”
Section: The Overlap Of Redox Proteomics and Transfusionmentioning
confidence: 98%
“…The in vitro hypotonic shock response assay, which tests the capacity of platelets to recover their initial shape after hypotonic stimulation, showed different results for control platelets versus PI-treated platelets [24,91,92]. It would be interesting to verify the correlation between ROS imbalance and poorer cell shape recovery.…”
Section: Role Of Redox Cysteine In Plateletsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the photoinactivation process using UV light, in particular UVC or UVB with riboflavin or UVA (much less efficient for oxidation) with amotosalen, reactive oxygen species are generated. It has been demonstrated that reactive oxygen species can induce modifications of model peptides and that this oxidative process could occur at the protein level and lead to protein modifications …”
Section: Discussionmentioning
confidence: 99%
“…After the inactivation process, riboflavin (vitamin B2) does not need to be removed from the treated product. The procedure is safe and is not toxic or carcinogenic [65, 67, 70], but may be associated with undesirable side effects such as expression of active GPIIb/IIIa on platelets and abnormal interaction of fibrinogen [88]. This method has recently been shown to efficiently inactivate dengue virus in platelet concentrates [89], ebola virus in vitro [90] and P. falciparum in whole blood, as described above [59].…”
Section: Techniques For Pathogen Reduction/inactivationmentioning
confidence: 99%